Optical road‐ice detector operating in the near infrared. Issue 5 (1st February 2013) - Colace, L.; Santoni, F.; Assanto, G.
Abstract : Introduced is an optical approach for the assessment of the road conditions due to various atmospheric perturbations, such as the presence of ice and rain. The technique is based on measuring the polarisation contrast in reflection, in conjunction with the intensity of the diffused light, in the near infrared.